Eksistensi Tharîqat Ni’mat al-Lâhiyyah dalam Syi’ah - Abduh, M. Arrafie (TAJDID, 2016)
Tarekat Ni’matullahiyah (Allah pleasent Order) was founded by Shah Ni'matullah Wali and had spread across world parts of Asia, Europe, America, and Africa. London is the center of this tarekat teachings in the West, but it seems that it does not unfold its wings in Southeast Asia yet i.e. in Malay world especially in Indonesia, despite of Shiite teachings influenced the culture of its community, i.e., Barzanji (History of Muhammad Prophet life, according to Islamic Ensyclopaedia, explaned that al-Barzanji rises  in order circle) and  War Tale of Malay World in Riau. Tarekat Ni’matullahiyah refused fatalistic, static, excessive, alienation and ascetic paradigm of tarekat  (khalwat, zuhd and suluk) practice that cause to decrease and poverty. Nevertheless, the adherents of this tarekat strives to free themselves from any bunches and attentions both of physically and spiritually (dzikr and fikr or meditation and contemplation) as facilities for attaining the more gracious and eternal objective. It is just exactley on account of that Allah pleasant Order is a dynamic, humanistic, cosmopolite and sophisticate order. e core of Sufi’s doctrine that is developed in tarekat ritual system functions to strengthen spirituality and morality of the tarekat community. Different Sufi’s doctrines in each tarekat result in different social-political relationship among those three tarekat communities. Second, the social-political roles, relationships and participations of the tarekat community change along with the political changes of the government that ruled both in colonial era and in the Indonesian independence. Third, the social-political movement of the tarekat community can be differentiated into: inclusive-pragmatism of Godebag community, exclusivism-fundamentalism of Wara’i community, and fundamentalism-pragmatism of Tijani com-munity. Fourth, tarekat community movements promote spiritual and moral public education in social-political life in Indonesia . Based on the findings, it can be concluded that social-political movements of tarekat community are in line with Sufi’s doctrines that change into various movement types. Therefore, tarekat community is predicted to develop changing social-political movements.